2017
DOI: 10.1017/s1365100517000517
|View full text |Cite
|
Sign up to set email alerts
|

The Anchoring of Inflation Expectations in the Short and in the Long Run

Abstract: This paper introduces structural VAR analysis as a tool for investigating the anchoring of inflation expectations. We show that U.S. consumers' inflation expectations are anchored in the long run because macro-news shocks are long-run neutral for long-term inflation expectations. The identification of structural shocks helps to explain why inflation expectations deviate from the central bank's target in the short run. Our results indicate that the recent decline of long-term inflation expectations does not res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…Although short-and long-term inflation expectations of both groups show downward trends after 2014, no significant relationship is demonstrated between these two time series. The result is consistent with Nautz et al (2016), implying that the decrease in long-term inflation expectations observed in Figure 1 can be attributed to downward adjustments of consumers' expected or perceived inflation targets.…”
Section: Coherence Analysissupporting
confidence: 82%
See 4 more Smart Citations
“…Although short-and long-term inflation expectations of both groups show downward trends after 2014, no significant relationship is demonstrated between these two time series. The result is consistent with Nautz et al (2016), implying that the decrease in long-term inflation expectations observed in Figure 1 can be attributed to downward adjustments of consumers' expected or perceived inflation targets.…”
Section: Coherence Analysissupporting
confidence: 82%
“…This may to a certain extent explain the change in the lead-lag relationships between consumers' short-and long-term inflation expectations. Similar to the crisis period, the deanchoring of long-term inflation expectations is additionally observed in the period of 1993-1995, during which the U.S. was in turbulent times with the volatility of inflation expectations being high (Nautz et al, 2016). For high scales, relatively stable relationships emerge before 1997 and after 2006, with arrows pointing to the southeast.…”
Section: Coherence Analysismentioning
confidence: 75%
See 3 more Smart Citations